ANALISIS PENGARUH SERAT LIMBAH TEFLON TERHADAP SIFAT MEKANIK KOMPOSIT FIBER SEBAGAI MATERIAL PENGGANTI ALAS COR BETON - Hendra Aryanta; Abdullah Ma’ruf; Khanif Khoirul F; Nurida Finahari (ROTOR, 2017)
Teflon wastes are slightly difficult to recycle because the recycle products have different characteristic. Teflon wastes in flake form can used as alternative composite material. This research is aimed to get the effect of teflon waste due to mechanical properties of fiber composite. The research is done with laboratory experiments. Three different kind of Teflon which are white, blue and grey are studied. Teflon fiber compositions are varied as 0, 50, 70 and 90% of composite volume. The fibers are varied in length as 2, 3 and 4 cm, with 1 mm in width and thickness. Tensile tests are conducted for specimens with ASTM D-4762 standard. Charpy impact tests are conduct for specimens with with ASTM E 23 standard. The crack of the specimens are visualized with a digital camera. The result shows that Teflon fiber has effect due to mechanical properties. White Teflon tend to have greater tensile and impact strength rather grey and blue Teflon. The increase of Teflon composite volume tends to increase tensile and impact strength. Teflon length also tends to increase tensile and impact strength. Keywords: teflon, waste, composite, mechanical properties